On the Role of C1-Inhibitor as Inhibitor of Tissue-type Plasminogen Activator in Human Plasma - Huisman, L G M; van Griensven, J M T; Kluft, C (Thrombosis and Haemostasis, 1995)
An enzyme immuno assay was developed to measure complexes of tissue-type plasminogen activator (t-PA) with C1-inhibitor in order to study the role of C1-inhibitor as an inhibitor of t-PA in plasma. In vitro experiments with melanoma and recombinant t-PA learned that purified C1-inhibitor reacts with both single chain t-PA and two chain t-PA. The rate constants ranged from 3.0 to 5.2 M-1s-1 In plasma, melanoma and recombinant two chain t-PA were hardly inhibited by C1-inhibitor, in contrast to melanoma and recombinant single chain t-PA which were inhibited to the same extent by endogenous C1-inhibitor as they were by purified C1-inhibitor. In vivo, t-PA/C1-inhibitor complex could be measured in plasma in a few cases in healthy volunteers (0.62 ± 0.43 ng/ml t-PA equivalents), after exercise (0.84 ± 0.25 ng/ml t-PA equivalents) and after a desmopressin infusion (0.26 ± 0.04 ng/ml t-PA equivalents). However, t-PA/C1-inhibitor complex was found in plasma in all cases after venous occlusion (1.7 ± 0.5 ng/ml t-PA equivalents), in peritoneal fluid from patients suffering from peritoneal inflammatory disease (2.2 ± 1.3 ng/ml t-PA equivalents) and in plasma from healthy volunteers during a t-PA infusion (27.7 ± 18.5 ng/ml t-PA equivalents at peak level). In the last case, about 8 % of the infused dose of recombinant t-PA (alteplase) was inhibited by C1-inhibitor at peak level. The half-life (t1/2α) of t-PA antigen in plasma was found not to be altered when t-PA was inhibited by C1-inhibitor (4.0 min and 4.2 min, respectively). Thus, in vivo, t-PA/C1-inhibitor complex is mostly present when t-PA escapes rapid liver clearance and accumulates in one place (e.g. during venous occlusion or in peritoneal fluid) or when it circulates in high concentrations (e.g. during t-PA infusion).